2020
DOI: 10.1016/j.robot.2019.103334
|View full text |Cite
|
Sign up to set email alerts
|

A robot-assisted bilateral upper limb training strategy with subject-specific workspace: A pilot study

Abstract: This paper proposes a new robot-assisted bilateral upper limb training strategy, focusing on the bilateral coordination of users' upper limbs. The strategy is implemented and evaluated on a bilateral upper limb rehabilitation device (BULReD) that is an Hbot mechanism actuated by two Maxon DC motors. The control system consists of a position controller, an admittance controller and an adaptive algorithm, where the BULReD stiffness is modified session by session based on training performance. This strategy is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Bilateral therapy refers to the mirroring principle in performing rehabilitation [4]. Where the impaired limb copies the movement of the functional limb (Figure 3), this gives the user whole control of the affected limb [20,21].…”
Section: Bilateral Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral therapy refers to the mirroring principle in performing rehabilitation [4]. Where the impaired limb copies the movement of the functional limb (Figure 3), this gives the user whole control of the affected limb [20,21].…”
Section: Bilateral Therapymentioning
confidence: 99%
“…End-effectors have been developed recently to provide bilateral rehabilitation training, where the impaired limb copies the movement of the unimpaired limb in a synchronized behavior [22]. Some researchers have reported that bilateral rehabilitation has the feature of activating the impaired hemisphere by making the left side and the right side of the body follow the same trajectory [21].…”
Section: According To the Robot Structuresmentioning
confidence: 99%
“…There are more and more people in the world suffering from spinal cord injuries (SCIs), with approximately 60% with cervical SCIs leading to tetraplegia [ 1 ], which can create severe arm disabilities, resulting in an inability to complete activities of daily living (ADLs) [ 2 ]. In addition, stroke is becoming the leading cause of permanent disabilities worldwide, with over 15 million new cases each year and 50 million stroke survivors [ 3 ]; more than two-third of all patients affected by stroke have impaired upper limb motor function and have difficulty in independently performing ADLs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the exoskeleton-based ULRR, the robots can resemble human limbs as they are connected to patients at multiple points and their joint axes match with human joint axes; training of specific muscles by controlling joint movements at calculated torques is possible, and the number of anatomical movements can exceed six; typical exoskeleton ULRRs are SUEFUL-7 [ 10 ], CADEN-7 [ 11 ], ARMin III [ 12 ], L-EXOS [ 13 ], ExoRob [ 14 ], RUPERT [ 15 , 16 ], BONES [ 17 ], ULEL [ 18 ], and Limpact [ 19 ]; nonetheless, increasing the number of movement parts increases the number of device modules, so the system setup becomes difficult; moreover, since the shoulder has a variable joint center, the mechanical design and control algorithms become more complicated [ 7 ]. By comparison, the end-effector type ULRRs are connected to patients at one distal point, and their joints do not match with human joints; force generated at the distal interface changes the positions of other joints simultaneously, making isolated movement of a single joint difficult [ 20 , 21 ]; the advantages of the end-effector type ULRRs are that they have a simple structure and less complex control algorithms and can avoid abnormal motion and posture of the target anatomical joints and specific muscles; typical end-effector type ULRRs are MIT-Manus [ 22 ], AMES [ 23 ], iPAM [ 24 ], PASCAL [ 25 ], Fourier M2 [ 26 ], EEULRebot [ 27 ], hCAAR [ 28 ], PARM [ 29 ], CASIA-ARM [ 30 ], Sophia-3 [ 31 ], and BULReD [ 2 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…During robot control, the purpose is to regulate the position and/or speed to assist human joints to achieve coordinated training (Proietti et al, 2016 ). Progress in kinematic coordination has been made in lower limb rehabilitation (Gui et al, 2017 ), such as space robots (Lu and Jia, 2019 ), dual-arm surgical robots (Wu et al, 2019 ), and bilateral robots (Miao et al, 2020 ), but there are few examples in upper limb rehabilitation. Brokaw et al ( 2013 ) implemented a time-independent functional training mode on the ARMin III robot, to realize the coordinated training for stroke patients.…”
Section: Introductionmentioning
confidence: 99%